2020
DOI: 10.1061/(asce)nh.1527-6996.0000342
|View full text |Cite
|
Sign up to set email alerts
|

If Mitigation Saves $6 Per Every $1 Spent, Then Why Are We Not Investing More? A Louisiana Perspective on a National Issue

Abstract: This paper provides an accounting of where and when mitigation and recovery investments have occurred in Louisiana, thereby generating a mitigation investment portfolio for the state. An exploratory data analysis of FEMA OpenData sets, supplemented by data on disaster damage and recovery, was conducted to develop a portfolio of mitigation actions implemented in the State of Louisiana since 1989 and to calculate damage to mitigation and recovery to mitigation expenditure ratios. Not surprisingly, Louisiana reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Educating vulnerable populations about the effect of tropical cyclones (most expensive disasters) and severe storms (high-frequency disasters) can signi cantly reduce the economic impact and save American lives. A dollar invested by the federal government in disaster mitigation saves six dollars in recovery (Gall & Friedland, 2020). A proactive measure and numerical modeling approach can substantially mitigate the adverse effects of highly disruptive disasters such as cyclones, severe storms, and drought (Hoffmann & Muttarak, 2017).…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…Educating vulnerable populations about the effect of tropical cyclones (most expensive disasters) and severe storms (high-frequency disasters) can signi cantly reduce the economic impact and save American lives. A dollar invested by the federal government in disaster mitigation saves six dollars in recovery (Gall & Friedland, 2020). A proactive measure and numerical modeling approach can substantially mitigate the adverse effects of highly disruptive disasters such as cyclones, severe storms, and drought (Hoffmann & Muttarak, 2017).…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…However, financial resources are frequently allocated disproportionately to support recovery initiatives after a disaster rather than using a few resources to finance pre-disaster mitigation activities. According to research, disaster mitigation investing is cost-effective because it typically generates $6 in savings for every $1 invested (Gall and Friedland 2020).…”
Section: Introduction 1climate Change and Natural Disastersmentioning
confidence: 99%
“…Pre-disaster mitigation and preparedness can reduce the disaster impact. For example, calculations from the United States demonstrated that a one-dollar pre-disaster mitigation investment could reduce 6-dollar losses from potential disasters (Gall & Friedland, 2020). Therefore, it is essential to discover the facilitators and barriers of pre-disaster mitigation and preparedness to reduce potential disaster losses in the uncertain world.…”
Section: Introductionmentioning
confidence: 99%